Tax Compliance Analysis Of Individual Income Taxpayers In The Era Of Tax Digitalization: Study At Indonesian Tax Office - Susena , Karona Cahya; Wulandari, Annisa; Hidayah , Nenden Restu (Journal of Management, Economic, and Accounting, 2025)
This study analyzes individual income taxpayer compliance levels in the context of tax digitalization in Indonesia. The main focus is identifying factors affecting tax compliance in the digital era and the effectiveness of digital tax system implementation in improving taxpayer compliance. Using a mixed-method approach involving 450 individual taxpayer respondents and secondary data from 10 Tax Offices, the research finds that digital literacy levels, system ease of use, and digital service quality significantly positively affect tax compliance. Results show a 24% increase in formal compliance and 18% in material compliance after digital tax system implementation. These findings provide important implications for digital taxation policy development in Indonesia.